The effect of tax incentives practices on the sustainability of micro, small and medium enterprises in Ethiopia during the outbreak of corona virus pandemic - Kanbiro Orkaido Deyganto (Journal of Innovation and Entrepreneurship, 2022)
This study was aimed to identify the effect of tax incentive practices on the sustainability of MSMEs during an outbreak of coronavirus pandemic in Ethiopia.
Keywords: 650; Corona virus pandemic; Ethiopia; Micro; Small and medium-sized enterprise; Sustainability; Tax incentives practices